Autoethnographic Reflections on Da’wah Representation in Rindu Suara Adzan 2024 - Budi Zaelani (PANTUN: Jurnal Ilmiah Seni Budaya, 2025)
The Rindu Suara Adzan 2024 religious-comedy soap opera depicts quotidian socioeconomic realities infused with Islamic principles, including humor and elements of contemporary culture. This article offers an autoethnographic reflection on the author's experience portraying "Mas Sugeng," utilizing Charles Sanders Peirce’s semiotic framework to analyze the visual and symbolic portrayal of da’wah. This study used a qualitative narrative approach to analyze four situations that illustrate the home, economic, and emotional aspects of masculinity within urban Indonesian society. The findings indicate that da’wah in religious meditation and television dramas functions not by verbal preaching but through nuanced emotional connection, humor, and approachable moral exemplars. The analysis illustrates how Sugeng’s gestures, objects, and silences represent inclusive Islamic messages, so converting entertainment into a participatory modality of popular da’wah. This study enhances comprehension of media Islamization, emotional piety, and cultural communication in postmodern Indonesia, positioning autoethnography as both a method and a performance within visual culture research.